ResQAlert / Siti Nurul Izza Hashim … [et al.] - Hashim, Siti Nurul Izza; Jusnyzan, Aini Nasira; Abdul Razak, Mastureena Marsya; Yazid, Nurul ‘Afina Nabilah; Mohd Shah Johan, Nayli; Wan Mohd Nadzir, Wan Irdina Syahirah; Za’aba, Zurrull-Aisya (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
ResQAlert presents a life-saving innovation aimed at assisting the deaf community during emergencies by providing timely alerts through visual cues on their devices. In Malaysia, where there are 42,652 registered hearing-impaired individuals as of January 31, 2023, the necessity for specialized emergency alerts for the deaf becomes evident. The lack of such alerts and the perceived inaccessibility of traditional systems underscore the urgency for a solution like ResQAlert. ResQAlert fills a significant gap in conventional systems by offering clear and accessible alerts through visual signals, such as flashing lights, thereby enhancing safety and independence for individuals with hearing loss. Its novelty lies in its practicality, demonstrated through smartphone connectivity, remote monitoring, and customizable alarms. By providing a clear and accessible method to be informed of critical sounds and warnings, ResQAlert promotes inclusivity, independence, and safety during emergencies. This study highlights the importance of creative solutions tailored to specific community needs, contributing to a more secure and welcoming society. ResQAlert stands as a vital innovation for the deaf community, offering a solution that addresses their unique challenges and enhances their quality of life.